FORM AND CONTENT: A HISTORICAL AND ARTISTIC ASSESSMENT OF A 17TH CENTURY ILLUSTRATED MANUSCRIPT OF SHAHNAMEH FROM S.M.N.A. LIBRARY, MALAYSIA - Zekrgoo, Amir H. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2018)
Shahnameh illustrated manuscripts are among the most sumptuous manuscripts produced in the history of Iran and within Persianate societies. The purpose of this research is to introduce and provide a multifaceted assessment of a 17th century illustrated manuscript of the Shahnameh, preserved at the Syed Muhammad Naquib Al-Attas Library MSS collection. In this study, after a brief introduction of the Shahnameh, the manuscript in hand is evaluated from historical, codicological and artistic perspectives. It identifies the calligraphic style(s), discusses the form of page layout and provides a compositional categorization of its 29 illustrations painted in Isfahan school style. In order to establish a meaningful text-image relation in terms of layout and composition the images are analyzed and categorized into three main divisions to facilitate artistic assessment. A graphic approach has been adopted to display the three categories in the format of schematic drawings which appear next to the images from the original illustrations. An overall evaluation of the physical condition of the manuscript is also provided to encourage taking measures for its preservation.